The Effectiveness of The Plant Tour Project Model PJJ 3 in One to Increase Statistical Literature Ability of High School Students on Plant Diversity - Aryati Aryati (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
Plant Tour Project PJJ 3 in One is a project-based distance learning model (Pembelajaran Jarak Jauh/PJJ) in identifying plants and processing statistical identification results involving three information technologies, namely PictureThis, Padlet and Quizizz. The purpose of this study was to determine the effectiveness of the Plant Tour Project Distance Learning 3 in One model in improving students' statistical literacy skills on plant diversity material. Experimental research with the type of One-Group Pretest-Posttest Design involved 36 samples of class XII MIPA SMAN 6 Bogor randomly selected. The research procedure is, students go on a tour to identify plants in their living environment using the PictureThis Artificial Intelligence (AI) application. Students online in groups process the results of statistical identification through the stages of understanding, analyzing, interpreting, evaluating and presenting data. The group project results are sent to the web tool Padlet for joint discussion and gamification using Quizizz. The validity of the instrument was tested by statistics and expert tests. The results of the pre-test and post-test were tested using the Paired Sample t Test, one tail, 5% significance level. The results showed that 76.11% of students were actively participating in learning, [t count] was 6.91 more than t table was 1.69 and there was an increase in learning outcomes by 53.46%, so it was concluded that the Plant Tour Project Distance Learning 3 in One model significantly effective in increasing students' statistical literacy skills on plant diversity material.